A precarious outcome of incidentally diagnosed Krukenbergs tumor in antepartum eclampsia case: a rare case report and review of literature - Thirupathi, Kalaivani; Mega Nathan, Jayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Kruckenbergs tumors are the rare metastatic tumors of ovary with its incidence of 1-2%. It’s occurrence along with pregnancy is very rare with reported incidence of 0.4-0.5%. The occurrence of Krukenbergs tumors along with gestational hypertension is also very rare and it has poor prognosis. The most common primary origin is from gastric site. We report a case of 28‑year‑old pregnant female presented with Antepartum Eclampsia with incidental findings of bilateral enlarged ovaries during caesarean section. The diagnosis of Krukenbergs tumor was made with histopathology and it’s primary origin was rendered by postoperative gastroscopy guided biopsy. Our case is enthralling in view of its unusual presentation, young age, and the diagnostic dilemma it poses. Our case report highlights the fact that early diagnosis of Krukenbergs tumor in pregnancy may be difficult at times owing to the masquerading effects, implying widespread metastasis and a poor maternal survival. Tumor resection with concomitant Chemotherapy was given as treatment. The main aim of this paper is to evaluate whether earlier diagnosis can be made in such cases. A thorough literature review was also conducted, unfortunately no methods can be used for early detection. Furthermore, no consensus regarding diagnostics or treatment avail till date. Hence the need for more research regarding this rare condition to offer recommendations about early detection, diagnosis and therapeutic approaches can be prompted.